The Use of Number Cards to Improve the Beginning Counting Skills of Second Grade Students at SD Muhammadiyah 01 Medan - Setiawani, Indah; Elfrianto, Elfrianto (EduMatika: Jurnal MIPA, 2025)
This study was initiated by the issue of low arithmetic skills among students in mathematics learning. The objective of this research was to explore the extent to which early arithmetic skills could be improved through the implementation of number card media among second-grade students at SD Muhammadiyah 01 Medan. The method employed was Classroom Action Research (CAR), conducted over two Cycles. Each Cycle consisted of the stages of planning, action implementation, observation, and reflection. Data collection techniques included direct observation and documentation. The findings revealed that the integration of number card media had a significant impact on enhancing students’ early arithmetic skills. This was evidenced by an increase in the percentage of students achieving learning mastery from 47% in Cycle I to 96% in Cycle II. Thus, there was a 49% improvement, indicating that the predetermined success indicators had been successfully met.